Integrating the Value of Sincerity in Hadith Learning into Contemporary Academic Work Ethic - Siti Humaira; Adi Saputra; Muhammad Aulia; Riyan Darwis (Al-Bukhari : Jurnal Ilmu Hadis, 2026)
This study investigates the integration of the prophetic value of sincerity (ikhlas), derived from hadith literature, into the contemporary academic work ethic. Within the modern higher education landscape, systemic pressures surrounding publication metrics and institutional prestige frequently shift scholarly focus from a genuine pursuit of knowledge toward transactional productivity. Employing a qualitative-descriptive library research method, this paper utilizes takhrij al-hadith (hadith authentication), matn (textual) analysis, and contextual interpretation of prophetic traditions regarding the virtues and dedication of seeking knowledge (talab al-'ilm). Positioned as a purely text-based inquiry, this study bypasses field research to focus strictly on hadith texts and their implementation within modern Islamic education. The findings demonstrate that the prophetic traditions heavily emphasize foundational virtues—such as sincere intention (niyyah), discipline, perseverance, consistency (istiqamah), and accountability—which serve as the bedrock for robust academic motivation. These values not only elevate the intellectual capacities of learners but also fortify their moral, spiritual, and social character. Furthermore, this study argues that ikhlas, when properly conceptualized, does not diminish professional output; instead, it refines the academic work ethic by fostering intellectual honesty, mitigating professional burnout, and instilling a profound sense of social responsibility. Practically, these insights provide a strategic framework for educators and Islamic academic institutions to cultivate a scholarly culture rooted in rigorous discipline, integrity, and spiritual values, proving that the prophetic ethos of learning remains deeply relevant to contemporary Islamic education.